Between Politicization and Securitization: Coverage of the European Migration Crisis in Czech Online News Media - Michal Tkaczyk (Communication Today, 2025)
According to polls, the proportion of Czech respondents who perceived irregular migration as a real and serious security threat doubled from 32% in 2014 to 65% in 2015. By means of a content analysis of the news stories published by three Czech online news portals, this study examines the extent to which images of a threat and an appeal for security were part of the media coverage of the European migration crisis. While only small differences in extent were observed among the three portals, the findings suggest that the crisis was depicted mainly in terms of governance, i.e. as a burden to the state or as a security threat. All three news portals gave prominence to qualities like urgency, extraordinariness, overload and insecurity, and attributed these qualities to the figure of an indefinite wave of migrants heading to Europe. The humanitarian dimension of the reported events was marginalised. The findings indicate a striking dependence on institutional sources, mainly government officials. Almost exclusive salience was given to the governmental agenda. Authorship of every other news story was assigned to the Czech Press Agency. Aforementioned partial characteristics of the coverage resulted in highly politicized image of the crisis, which to considerable extent was presented as a security threat.